On the structural interpretation of the Smets-Wouters "risk premium" shock - Jonas D. M. Fisher (Federal Reserve Bank of Chicago, 2014)
This article shows that the "risk premium" shock in Smets and Wouters (2007) can be interpreted as a structural shock to the demand for safe and liquid assets such as short-term US Treasury securities. Several implications of this interpretation are discussed.
Keywords: E00; E1; E3; E4; E5; G1; 330; Smets-Wouters model; safe and liquid assets; money demand; risk premium shock; New Keynesian model; DSGE; flight-to-quality; liquidity preference